Noise Risk Assessment for Spooling Process in Manufacturing Industry - Zuhuri, Muhammad Zaffhuan Aieman; Amir Haziq Abd Razak; Mak Wan Hussain (Progress in Engineering Application and Technology, 2024)
This research undertakes a comprehensive assessment of noise risks within the spooling area of an industrial facility, with a specific focus on the recently installed spooling machine. The primary goal is to conduct a quantitative measurement and analysis of noise levels in the operational phase of the new machine, utilizing a noise level meter for precise readings. The second objective involves a comparative analysis, comparing noise data from the new spooling machine with historical data from the current machine. This comparative approach seeks to identify notable variations, offering insights into potential improvements for noise reduction strategies. The ultimate aim of the study is to propose practical engineering controls for minimizing noise levels, potentially recommending the integration of noise-absorbing machinery or an upgrade to the existing spooling machine. By addressing these objectives, the research seeks to contribute to a safer and more conducive working environment in the spooling area, emphasizing the importance of effective noise management strategies in industrial settings and highlighting the role of engineering controls in mitigating potential risks associated with elevated noise levels.